2009
DOI: 10.3766/jaaa.20.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Development of the North American Listening in Spatialized Noise–Sentences Test (NA LiSN-S): Sentence Equivalence, Normative Data, and Test–Retest Reliability Studies

Abstract: The NA LiSN-S is a potentially valuable tool for assessing auditory stream segregation skills in children. The availability of one-sided critical difference scores makes the NA LiSN-S useful for monitoring listening performance over time and determining the effects of maturation, compensation (such as an assistive listening device), or remediation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…Several previous studies have also found no significant effect of age under at least some conditions (Litovsky, 2005;Garadat and Litovsky, 2007). Some previous studies have found a significant effect under some conditions, but the direction of the effect varies between studies and/or conditions Litovsky, 2005;Cameron and Dillon, 2007;Cameron et al, 2009;Vaillancourt et al, 2008;van Deun et al, 2010). We hypothesize that when the target and masker are dissimilar (i.e., low informational masking) and there is reverberation present, the SRM is small, and there is little or no effect of age.…”
Section: B Srm: Effect Of Age and Hearing Thresholdsmentioning
confidence: 66%
See 3 more Smart Citations
“…Several previous studies have also found no significant effect of age under at least some conditions (Litovsky, 2005;Garadat and Litovsky, 2007). Some previous studies have found a significant effect under some conditions, but the direction of the effect varies between studies and/or conditions Litovsky, 2005;Cameron and Dillon, 2007;Cameron et al, 2009;Vaillancourt et al, 2008;van Deun et al, 2010). We hypothesize that when the target and masker are dissimilar (i.e., low informational masking) and there is reverberation present, the SRM is small, and there is little or no effect of age.…”
Section: B Srm: Effect Of Age and Hearing Thresholdsmentioning
confidence: 66%
“…We hypothesize that when the target and masker are dissimilar (i.e., low informational masking) and there is reverberation present, the SRM is small, and there is little or no effect of age. This contrasts with tests performed under essentially anechoic conditions, and where the target and masker are easily confused (i.e., high informational masking), where the SRM is large and increases with age (Cameron and Dillon, 2007;Cameron et al, 2009). It may be that the fewer cues available to separate the target from the competition, the more likely it is that spatial advantage increases with age.…”
Section: B Srm: Effect Of Age and Hearing Thresholdsmentioning
confidence: 87%
See 2 more Smart Citations
“…Auditory segregation skills were measured using the North American Listening in Spatialized Noise-Sentence Test (NA LiSN-S) [29]. Target sentences are spoken by a female in the presence of a competing signal that is either the same female voice or a male voice narrating a story.…”
Section: Behavioral Measuresmentioning
confidence: 99%